Vasily Fedorovich Fon Baumgarten and His Role in Yugoslav Interwar Architecture - Prosen, Milan I. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The architectural oeuvre of Vasily Fedorovich von Baumgarten (1879–1962) was discussed in architectural writings during his lifetime. Owing to its undeniable social, urban, and artistic significance, mentions and analyses of his works often appeared in panoramic surveys of interwar architecture and in historiographic narratives on the contribution of Russian émigré architects. Although research into Baumgarten’s oeuvre began in the early 1990s, more recent studies in Serbian and Russian historiography have provided a fuller picture of his small yet highly significant and unfortunately endangered body of work. Between 1924 and 1940, Baumgarten designed several buildings whose importance in the architectural development of Yugoslavia places him among the leading Russian émigré builders. Notable among them are the General Staff of the Army and Navy of the Kingdom of SCS/Yugoslavia in Belgrade (1924–1928), the Officers’ House in Skopje (1925–1929), the Russian House of Emperor Nicholas II in Belgrade (1930–1933), and the Mortgage Bank in Valjevo (1938–1939). His oeuvre demonstrates exceptional stylistic polymorphism, reflecting a flexible approach to each commission. It encompasses Russian academism, Empire style, Neo-Renaissance, Art Deco, and Monumentalism, as well as the Serbian national style, exemplified by his design for the Gračanica Monastery dormitories in 1933. Baumgarten’s noble origin, education at leading institutions in St. Petersburg, military career and rank of major general, together with his architectural achievements prior to arriving in Belgrade, secured him a respected position within the Russian émigré community. As president of several artistic associations of exiled artists from the former Russian Empire, he organized and participated in joint exhibitions during this period. Despite his prominence, not all of his works have been preserved; some no longer exist in their original form and remain endangered, underscoring the need for their protection. After leaving Yugoslavia in 1948/49, Baumgarten settled in Argentina, where he lived and worked until his death.
Keywords: Baumgarten; interwar architecture; Empire style; Yugoslavia; Russian emigration; Art Deco